Polyvinyl alcohol (PVA) based gel electrolytes: Characterisation and applications in Dye-sensitized solar cells / Mohd Fareezuan Abdul Aziz - Mohd Fareezuan , Abdul Aziz (2017)
Three systems of gel polymer electrolytes have been prepared in this work. First system was PVA-DMSO-EC-PC-KI-I2 gel polymer electrolytes. In the first system, various amount of KI salt were added. The highest conductivity of gel polymer electrolyte for the first system was 12.50 mS cm-1 for the gel polymer electrolyte with the composition of 5.58 wt. % of PVA - 8.37 wt. % of EC - 11.16 wt. % of PC - 61.37 wt. % of DMSO - 11.72 wt. % of KI - 1.80 wt. % of I2. To this composition, part of KI was replaced with the quaternary ammonium iodide salt which is TMAI, TPAI and TBAI for the second system. The conductivity of the gel polymer electrolyte decreased with the increasing amount of quaternary ammonium iodide salts. The best electrolyte in systems 2 which gave the highest efficiency of 5.51 % and 5.80 %, respectively have been chosen for incorporation with diethyl carbonate (DEC) plasticizer (systems 3). With the addition of DEC plasticizer, the conductivity of the gel polymer electrolyte and efficiency of DSSC were enhanced. The highest efficiency of 7.5 % was obtained for the DSSC having 5.47 wt. % of PVA - 8.21 wt. % of EC - 10.95 wt. % of PC - 60.22 wt. % of DMSO - 3.45 wt. % of KI - 8.05 wt. % of TBAI - 1.08 wt. % of I2 - 2.57 wt. % of DEC. The interaction of gel polymer electrolytes have been studied via fourier transform infrared (FTIR) spectroscopy. The peak shifting observed for S=O, O-H, C-O-C and C=O bands indicates that the interaction has occurred. X-ray diffraction (XRD) pattern reveals that all gel polymer electrolytes are amorphous.